Speaking Irish with hurley sticks: Gaelic sports, the Irish language and national identity in revival Ireland. Issue 1 (2nd January 2017) - Billings, Cathal
ABSTRACT: The Gaelic Athletic Association (GAA) ban on foreign games, implemented nationally in 1905, affected not only GAA members but Gaelic League members also. The shared Gaelic heritage of both organisations led to their marriage in the Irish Ireland movement and the aims and ideals of both organisations were promoted alongside one another. GAA members were expected to promote and use Irish while Gaelic League members were to play only Gaelic sports. The commitment of GAA members to the language was to prove controversial throughout the Irish revival period, however, where lip service, symbolism and general lack of interest in the language led to the diminishing of GAA language policies. Nevertheless, GAA members enjoyed the status of being uniquely Gaelic. The same leniency was not afforded to Gaelic Leaguers with regard to vigilance in games. By tying itself to the GAA and the ban, the Gaelic League compromised its own ideals as regards the language forming the basis of Irish nationality and the importance of the games as part of Gaelic identity greatly increased. This corresponds with Timothy G. McMahon's argument that the secondary aims of the Gaelic League came to obtain greater prominence in the Gaelic Revival than the language itself.